2007
DOI: 10.1507/endocrj.k06-201
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism is Related to Lower Heel QUS in Postmenopausal Women

Abstract: Abstract. Recent findings suggest that thyroid stimulating hormone (TSH) is a negative regulator of skeletal remodeling by reducing both differentiation of osteoblasts and formation of osteoclasts. In addition, increased fracture risk in untreated hypothyroid patients has been reported to begin up to 8 years before diagnosis. The aim of the present study was to evaluate the effect of subclinical hypothyroidism on bone structure by using the heel QUS. Subjects were outpatients without any past or present histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
(31 reference statements)
1
14
0
3
Order By: Relevance
“…The results of the study showed that men with high TSH levels, but lower than 10 mIU/L, had an increased risk of fracture, thus suggesting that even mild subclinical hypothyroidism may have deleterious effects on bone. Moreover, Nagata et al [37] recently reported that calcaneus osteosonographic assessment indices of right feet, measured using the quantitative ultrasound, were lower in postmenopausal women with SH than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that men with high TSH levels, but lower than 10 mIU/L, had an increased risk of fracture, thus suggesting that even mild subclinical hypothyroidism may have deleterious effects on bone. Moreover, Nagata et al [37] recently reported that calcaneus osteosonographic assessment indices of right feet, measured using the quantitative ultrasound, were lower in postmenopausal women with SH than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation was especially strong between increasing serum TSH within the reference range and increasing bone mass in both Caucasian and African American women [42]. Another prospective study showed that euthyroid women with serum TSH in the lower tertile of the normal range had a higher incidence of vertebral fractures; these findings were independent of age, BMD, and thyroid hormones [60,61].…”
Section: Tsh and Clinical Evidencementioning
confidence: 94%
“…There was a particularly strong correlation between increasing serum TSH within the reference range and increasing bone mass in both black and white American women [20]. Finally, in limited observations, serum TSH in patients receiving thyroxine has been correlated with indices of bone microarchitecture in vivo, using heel ultrasound measurements, but no fi rm conclusions can be drawn from these studies [40]. Thus, though it is clear that TSH levels correlate positively with bone density and are inversely related to bone turnover markers, a cause-effect relationship is unlikely to emerge from such studies.…”
Section: Clinical Correlations Between Serum Tsh and Bone Massmentioning
confidence: 94%